(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The informal sector in India comprises a significant portion of the workforce, yet it remains largely underserved in terms of financial services, including life insurance. This research paper explores the challenges and opportunities of increasing life insurance penetration in the informal sector in India. Through a thorough review of the literature, analysis of existing data, and interviews with key stakeholders, the paper highlights the barriers to access and adoption of life insurance in the informal sector, as well as potential strategies to overcome them. The findings of this paper can apprisepolicymakers, insurance companies, and other stakeholders on how to better serve the needs of the informal sector and increase financial inclusion in India. India's life insurance sector, despite witnessing significant reforms, faces a critical challenge: low penetration, particularly within the vast informal sector. This research paper delves into the complexities of this issue, analysing the challenges that hinder life insurance acceptanceamong informal workers and exploring the untapped opportunities for growth. The paper examines factors such as financial literacy, product design, distribution channels, and regulatory frameworks, identifying their impact on insurance penetration. Additionally, it explores innovative approaches, technological advancements, and government initiatives that can bridge the gap and enhance insurance inclusion for the informal workforce.